2019
DOI: 10.1177/2516103219874810
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of stability and change in the mental health of children who grow up in family-based out-of-home care

Abstract: The present review sought to address the following questions: What evidence is there that long-term, family-based out-of-home care (OOHC) has a general, population-wide effect on children’s mental health such that it is generally reparative or generally harmful? Does entry into long-term OOHC affect children’s mental health, as evidenced by prospective changes over the first years in care? And, is the reparative potential of long-term, family-based OOHC moderated by children’s age at entry into care? Fourteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The Looking more closely across the 11 profiles, we can see that none of them include clinical range CBCL affective problems or anxiety problems. This is unsurprising given that previous surveys have consistently found that children and adolescents in care are reported with lower internalizing difficulties relative to other difficulties on general measures such as the CBCL and SDQ (Goemans et al, 2015;Tarren-Sweeney & Goemans, 2019). However, it is notable that Profiles #7 and #11 are characterized by clinical-level ACA dissociation / trauma symptoms alongside sub-clinical CBCL anxiety problems.…”
Section: Cbcl-dsm/aca Profilesmentioning
confidence: 95%
“…The Looking more closely across the 11 profiles, we can see that none of them include clinical range CBCL affective problems or anxiety problems. This is unsurprising given that previous surveys have consistently found that children and adolescents in care are reported with lower internalizing difficulties relative to other difficulties on general measures such as the CBCL and SDQ (Goemans et al, 2015;Tarren-Sweeney & Goemans, 2019). However, it is notable that Profiles #7 and #11 are characterized by clinical-level ACA dissociation / trauma symptoms alongside sub-clinical CBCL anxiety problems.…”
Section: Cbcl-dsm/aca Profilesmentioning
confidence: 95%
“…School professionals may be hesitant to assess a child in foster care for ASD because of the presence of recent trauma exposure. There may be an over‐reliance on the perspective that the negative effects of trauma on development may dissipate over time in a stable environment and that a child's symptoms may be significantly different in a year or two (Dubowitz et al, 2016; Tarren‐Sweeney & Goemans, 2019). However, while some children who experience trauma demonstrate improvement over time, others do not.…”
Section: Recommendations and Future Directionsmentioning
confidence: 99%
“…Previous literature reviews and meta-analyses examining the development of youths' mental health problems in out-of-home care have found that general behavioral problems were stable during foster care [14,15]; no evidence was found that growing up in care is generally ameliorating or detrimental for children who enter care [16]. In jurisdictions where children predominantly enter care following severe and persistent maltreatment, a child's age at entry https://doi.org/10.1192/j.eurpsy.2022.…”
Section: Introductionmentioning
confidence: 96%